Literasi Statistik pada Pembelajaran Siswa SMP melalui Model Quantum Synesthetic Learning Berbasis Media Digital Terapan dalam Prespektif Kecerdasan Majemuk - Herla Nur Deswana Fitri; Arezqi Tunggal Asmana; Abdur Rohim (Mataram University, 2026)
Differences in how students interpret statistical information indicate that successful statistical literacy is determined not only by conceptual understanding but also by the characteristics of the intelligences they employ when interacting with data. This issue is particularly relevant in Quantum Synesthetic Learning supported by digital media, where data serve as the central focus of learning activities through multiple forms of representation. This study aimed to describe junior high school students' statistical literacy from the perspectives of logical-mathematical, visual-spatial, and interpersonal intelligences. A descriptive qualitative approach was employed involving 30 seventh-grade students from MTs Putra Putri Simo. Data were collected through a multiple intelligences questionnaire, a statistical literacy test, and semi-structured interviews. The findings revealed that students with logical-mathematical intelligence achieved a very high level of statistical literacy, characterized by systematic numerical reasoning in making decisions. Students with visual-spatial intelligence attained a high level by relying on pattern recognition and graphical representations, whereas students with interpersonal intelligence also demonstrated a high level by examining relationships among pieces of information before drawing conclusions. These findings suggest that different types of intelligence shape distinct pathways of statistical literacy, even when students participate in the same learning environment.